DENDROECOLOGICAL ANALYSIS OF Ocotea pulchella Nees et Mart. ex Nees (CANELA LAGEANA) IN THE SERRA GERAL OF SANTA MARIA, RS, BRAZIL - Spatelf, Peter (2000)
The relationship between climatic variables and stem diameter increment of five Ocotea pulchella trees was studied on  a water-influenced site in Itaára, RS. Growth  data  was  obtained by stem analysis. On the stem disks taken at breast height diameter (1.3 m), radial increment was measured on four perpendicular radii. The mean growth sequences were standardized to highlighten short-term variation. Climatic data is originated from the meteorological station of Santa Maria, RS. Compound climatic quantities like evapotranspiration and water balance were calculated for better describing hydric conditions of tree growth. Pointer years and sensitivities of growth sequencies were calculated. Possible liberation of trees and its effect on radial growth was studied. Variation of increment and climatic variation was compared by using correlation analysis. No climatic pattern could be found which coherently influenced diameter increment during the observation period. However, excess of water seems to influence the variation of diameter increment on the studied site.